Jewish Life and Culture in Germany after 1945 Sacred Spaces, Objects and Musical Traditions - Keßler, Katrin; Ross, Sarah M.; Staudinger, Barbara; Weik, Lea (De Gruyter, 2022)
How was the re-emerging Jewish religious practice after 1945 shaped by traditions before the Shoah? To what extent was it influenced by new inspirations through migration and new cultural contacts? By analysing objects like prayer books, musical instruments, Torah scrolls, audio documents and synagogue rooms, this volume shows how the post-war communities created new Jewish musical, architectural and artistic forms while abiding by the tradition.